Evaluation of anti-Bothrops asper venom activity of ethanolic extract of Brownea rosademonte leaves - Salazar Marcos; Chérigo Lilia; Acosta Hildaura; Otero Rafael; Martínez-Luis Sergio (Acta Pharmaceutica)
Significant inhibition of the coagulant and hemorrhagic effects of Bothrops asper venom was demonstrated by ethanolic extract prepared from the leaves of Brownea rosademonte. In vitro experiments preincubating 5.5 mg of extract kg-1 b.m. for 30 min with a minimum hemorrhagic dose of venom (273.8 ± 16.1 μg of venom kg-1 b.m.) lowered the hemorrhagic activity of the venom alone in CD-1 mice by 51.5 ± 2.6 %. Additionally, 1.7 mg extract L-1 plasma prolonged 5.1 times the plasma coagulation time. Fractionation of the extract led to the isolation of two compounds: ononitol (1) and quercetrin (2). The structure of compounds 1 and 2 was established by spectroscopic analyses, including APCI-HRMS and NMR (1H, 13C, HSQC, HMBC and COSY). A quercetrin concentration of 0.11 μmol L-1 prolonged the plasma coagulation time 2.6 times demonstrating that this compound was one of the active constituents of the Brownea rosademonte extract.